1984
DOI: 10.1111/j.1600-079x.1984.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Cytoplasmic Inclusion Bodies in Pinealocytes of the Cotton Rat, Sigmodon hispidus: An Electron Microscopic Study

Abstract: Electron microscopic observations on pinealocytes of cotton rats (Sigmodon bispidus) killed in October revealed the presence of cytoplasmic inclusion bodies (CIBs) and two kinds of nuclear inclusions--coiled bodies and granular inclusion bodies. These inclusions were usually not bounded by a membrane. CIBs showed round or irregular profiles and consisted of granular and filamentous materials of moderate electron opacity intermingled with electron-lucent areas. Nuclear granular inclusions appeared as homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The ultrastructure of the cotton rat pinealocyte has been recently described in detail [Matsushima et al, 1979[Matsushima et al, , 1984Karasek et al, 1982;1983b,c). Therefore, here we include only a typical electron micrograph of that cell ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ultrastructure of the cotton rat pinealocyte has been recently described in detail [Matsushima et al, 1979[Matsushima et al, , 1984Karasek et al, 1982;1983b,c). Therefore, here we include only a typical electron micrograph of that cell ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, NLBs have been described as an accumulation of fine flocculent material in the pineal gland and it was suggested that this contains 5-hydroxytryptamine (5-HT) (Machado et al 1968). However, Matsushima et al (1984) observed that inclusion bodies in pinealocytes of the cotton rat appeared to contain protein and calcium and may represent NLBs, mineral deposits, secretory products or viral inclusions. In a previous study on dogs (Calvo et al 1988), two types of granules in pinealocytes were identified ultrastructurally as melanin.…”
Section: Discussionmentioning
confidence: 96%
“…These inclusion bodies may represent nucleolus-like bodies (NLBs), mineral deposits, or secretory products (Karasek et al 1983), as well as cytoplasmic inclusion bodies (CIBs) and two kinds of nuclear inclusions, coiled bodies and granular inclusion bodies. These bodies, components of the germinal vesicles (Inoue et al 2011), are not usually bounded by a membrane (Matsushima et al 1984). They are defined as NLBs (Fechner 1986;Kleshchinov 1989;Takeuchi 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The coiled body was first described in somatic cells as a 300-nm- (Monneron and Bernhard, 1969) to 900-nm wide sphere (Seite et al, 1982) composed of units called "threads" (Monneron and Bernhard, 1969;Bernhard, 1971;Sananes and Le Goascogne, 19761, "strands" (Kinderman and LaVelle, 1976;Matsushima et al, 1984) and hereafter "coils" (Kinderman and LaVelle, 1976;Schultz, 1989). The coils had a width varying from 30 nm (Lafarga et al, 1983a1 to 63 nm (Hervas et al, 1980.…”
Section: Coiled Bodymentioning
confidence: 99%